2019
DOI: 10.1049/mnl.2018.5583
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of TiO 2 nanoparticles/Fe 2 O 3 waste chips composite

Abstract: Water contamination along with the environmental issues resulted by industrial wastewaters have caused a trend in applying semiconducting photocatalysts, among which TiO 2 composites have been particularly focused on to overcome the drawbacks of titanium(IV) oxide also known as titania. In the current investigation, waste chips of a structural steel bar with the chemical composition of Fe 2 O 3 were utilised to obtain the TiO 2-Fe 2 O 3 composite. X-ray diffraction (XRD), field-emission scanning electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…However, the most commonly used organic pollutant is methylene blue, which is not suitable as a probe chemical for photocatalytic activity tests [25]. Several studies on the degradation of methyl orange employing TiO2/Fe2O3 composites revealed that the addition of Fe2O3 improves photocatalytic efficiency when exposed to UV light [26][27][28]. In this study, photodegradation of MO by TiO2/Fe2O3 composites was presented.…”
Section: Introductionmentioning
confidence: 92%
“…However, the most commonly used organic pollutant is methylene blue, which is not suitable as a probe chemical for photocatalytic activity tests [25]. Several studies on the degradation of methyl orange employing TiO2/Fe2O3 composites revealed that the addition of Fe2O3 improves photocatalytic efficiency when exposed to UV light [26][27][28]. In this study, photodegradation of MO by TiO2/Fe2O3 composites was presented.…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, it has demonstrated that the photocatalytic activity of SnO 2 is significantly improved when the metal oxide is coupled with either short or wide bandgap semiconductors [18]. It is well known that TiO 2 is the most commonly used semiconductor and with excellent photocatalytic performance [19]. Commonly, SnO 2 was selected to couple with TiO 2 to enhance its photocatalytic activity [20].…”
Section: Introductionmentioning
confidence: 99%